Prevalence of OXA-type Class D β-lactamases Among Clinical Isolates of Klebsiella Pneumoniae in Multiple Centers of Tehran, Iran - Mehrbakhsh, Pariya; Basharkhah, Yalda; Bahkshi, Ashraf; Kamarposhti, Lida Tahmasebi N.; Bolori, Shahin (Infectious Disorders - Drug Targets, 2021)
Background: Drug- and multidrug-resistant Klebsiella pneumoniae isolates have been found worldwide. Treatment failures against carbapenems and extended-spectrum cephalosporins, the currently recommended drugs, contribute to consider K. pneumoniae infections as untreatable infections. The emergence and spread of oxacillinases (OXAs) with carbapenem-hydrolyzing properties are a major concern and seriously become a public health problem worldwide. The present study was aimed to explore the blaOXA genes among clinical isolates of K. pneumoniae in some clinical settings in Tehran, Iran. Methods: A total of 90 K. pneumoniae isolates were collected from different clinical samples at hospitals in Tehran during the year 2016 and 2018. Antimicrobial susceptibility testing was performed on bacterial isolates using the Kirby-Bauer disc diffusion method on Mueller Hinton agar plates. PCR experiments were carried out to detect the presence of the blaOXA genes, including blaOXA- 1, blaOXA-2, blaOXA-4, blaOXA10, and blaOXA-48-like, using specific primers. Results: The antibiotics susceptibility results showed that 41% of the K. pneumoniae isolates were resistant to imipenem and meropenem. Resistance rates for cephalosporin agents, including cefpodoxime, ceftazidime, cefuroxime, cefotaxime, and cefepime, were measured as 72.3%, 67.8%, 67.7%, 65.5%, and 60%, respectively. In the present study, 51.1% of isolates were classified as multidrug-resistant K. pneumoniae strains. The molecular assays showed that 56.6% of isolates harbored blaOXA-2. In addition, blaOXA-4, blaOXA-1, blaOXA-10, and blaOXA-48-like genes were also found in 16.7%, 5.6%, 1.1%, and 1.1% of isolates, respectively. Conclusion: The spread of blaOXAs, especially blaOXA-48-like, among K. pneumoniae isolates indicated the inadequate dissemination control of multidrug-resistant bacteria in the Iranian hospital environment. There is a reason to assume that OXA producing K. pneumoniae will limit clinical therapeutic options in the future and pose threats to national public health among the Iranian population.
Keywords: imipenem